Small-molecule TFEB pathway agonists that ameliorate metabolic syndrome in mice and extend C. elegans lifespan. Issue 1 (December 2017) - Wang, Chensu; Niederstrasser, Hanspeter; Douglas, Peter; Lin, Rueyling; Jaramillo, Juan; Li, Yang; Oswald, Nathaniel; Zhou, Anwu; McMillan, Elizabeth; Mendiratta, Saurabh; Wang, Zhaohui; Zhao, Tian; et al.
Abstract Drugs that mirror the cellular effects of starvation mimics are considered promising therapeutics for common metabolic disorders, such as obesity, liver steatosis, and for ageing. Starvation, or caloric restriction, is known to activate the transcription factor EB (TFEB), a master regulator of lipid metabolism and lysosomal biogenesis and function. Here, we report a nanotechnology-enabled high-throughput screen to identify small-molecule agonists of TFEB and discover three novel compounds that promote autophagolysosomal activity. The three lead compounds include the clinically approved drug, digoxin; the marine-derived natural product, ikarugamycin; and the synthetic compound, alexidine dihydrochloride, which is known to act on a mitochondrial target. Mode of action studies reveal that these compounds activate TFEB via three distinct Ca2+ -dependent mechanisms. Formulation of these compounds in liver-tropic biodegradable, biocompatible nanoparticles confers hepatoprotection against diet-induced steatosis in murine models and extends lifespan ofCaenorhabditis elegans . These results support the therapeutic potential of small-molecule TFEB activators for the treatment of metabolic and age-related disorders. Activation of autophagy, via the transcription factor TFEB, is a promising strategy to treat metabolic diseases. Here, the authors report three novel classes of small molecules that promote TFEB nuclear translocation, and provide evidence for the therapeutic efficacy of these compounds in mice and worms.